WHITE COLLAR CRIME (KEJAHATAN KERAH PUTIH) DALAM PENEGAKAN HUKUM PIDANA - Syahdi Buamona (FAKULTAS HUKUM UM PAREPARE, 2019)
this paper analyzes several problems, namely what is the white collar crime and how the white collar crime in criminal law enforcement. using the method used is normative juridical as for the results of the research, first, white collar crime is basically done by certain people who have a position, occupation, and position and are well-known in the life of society. The officials actually use their power in the wrong way, without paying attention to the impact on society and the country. Second, in the aspect of criminal law enforcement, white-collar crime is a crime in a position offense as a criminal event committed by people who work for a government bureaucracy and / or cooperate with other people. As a result of their actions, as well as criminal acts of corruption will be detrimental to state finances and declared an act that violates the law, both in the form of violations and crimes regulated by law.